Observation Test of Durian (Durio zibethinus Murr.) from Several Regions in West Sumatera - Indriyani, Ni Luh Putu; Ihsan, Farihul; Hadiati, Sri; Budiyanti, Tri; Riska, Riska; Jumjunidang, Jumjunidang; Mansyah, Ellina; Muas, Irwan (Bioscience, 2024)
The open pollinating of durian produces diversity that allows for indigenous selection. The aim of the research is to raise the potential of the genetic resources of West Sumatran durian to become a new superior variety. Observation tests were carried out in Sijunjung, Tanah Datar, Padang Pariaman, Sawahlunto, and Pesisir Selatan The variables observed were qualitative and quantitative characters, using the descriptor for durian and guidelines for preparing horticultural variety descriptions. Observations of qualitative and quantitative characters were carried out on plants, stems, leaves, flowers and fruit. From the results of the observation test, 4 new superior varieties have been registered, namely Kalumpang Sijunjung with Minister of Agriculture Decree No: 039/Kpts/SR.120/ D.2.7/6/2014, Tambago Sungai Tarab with Minister of Agriculture Decree No:015/Kpts/SR.120/D.2.7/2/2016, Kunik Tandikek with Minister of Agriculture Decree No: 258/Kpts/SR.130/D/III/2021, Sawah Kubang with Minister of Agriculture Decree No:225/Kpts/PV.240/D /VI/2023 and one prospective of durian variety of Pesisir Selatan which which is currently being processed in registering local varieties. In order for new varieties to develop, there needs to be a development program from local governments to stakeholders.  Apart from that, activities to increase the potential of durian genetic resources in West Sumatera need to continue.